2020
DOI: 10.3390/cells9071693
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondria in Cancer Stem Cell Resistance

Abstract: Cancer stem cells (CSC) are associated with the mechanisms of chemoresistance to different cytotoxic drugs or radiotherapy, as well as with tumor relapse and a poor prognosis. Various studies have shown that mitochondria play a central role in these processes because of the ability of this organelle to modify cell metabolism, allowing survival and avoiding apoptosis clearance of cancer cells. Thus, the whole mitochondrial cycle, from its biogenesis to its death, either by mitophagy or by apoptosis, can be targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 237 publications
(436 reference statements)
0
51
0
Order By: Relevance
“…CSCs are a small subpopulation of cancer cells with stem cell-like characteristics, including quiescence, selfrenew, and slow cell cycle. A growing number of studies indicate conventional chemotherapeutics mainly target the bulk non-CSCs population instead of the rare CSCs population that indeed cause the clinical relapse [22]. Mechanism explorations reveal that CSCs are resistant to chemotherapy owing to their quiescent state, increased drug efflux, and activate DNA repair [23].…”
Section: Emt Program and Cscsmentioning
confidence: 99%
“…CSCs are a small subpopulation of cancer cells with stem cell-like characteristics, including quiescence, selfrenew, and slow cell cycle. A growing number of studies indicate conventional chemotherapeutics mainly target the bulk non-CSCs population instead of the rare CSCs population that indeed cause the clinical relapse [22]. Mechanism explorations reveal that CSCs are resistant to chemotherapy owing to their quiescent state, increased drug efflux, and activate DNA repair [23].…”
Section: Emt Program and Cscsmentioning
confidence: 99%
“…These characteristics of CSCs make them among the main failure factors of anticancer therapies. In fact, the ability of CSCs to evade programmed cell death leads to resistance to various chemotherapeutic agents, such as those used in leukemia, malignant melanoma, brain, head and neck cancers, and breast, colorectal, and pancreas tumors [ 51 , 57 , 58 , 59 ]. Furthermore, resistance to radiotherapy in brain and breast cancers has also been demonstrated.…”
Section: Apoptosismentioning
confidence: 99%
“…Furthermore, MOMP can induce cell death in an independent caspase process [ 64 , 65 , 66 , 67 ]. However, in some tumors, such as breast [ 68 , 69 , 70 ], ovary, and skin cancers, it has been shown that CSCs can evade death upon mitochondrial dysfunction [ 57 ]. Numerous investigations in colon or breast cancer cells have highlighted a correlation between increased aggressiveness and nonlethal caspase activation [ 71 , 72 , 73 ].…”
Section: Apoptosismentioning
confidence: 99%
“…Like HSCs, AML cells have unique mitochondrial and metabolic features with reliance on OXPHOS [ 158 ]. Recently, the mitochondrial transacylase tafazzin (TAZ) was demonstrated to regulate AML stemness by modulating intracellular levels of phospholipids [ 159 ]. This X-linked gene was identified by a clustered regulatory interspaced palindromic repeat (CRISPR) screen.…”
Section: Mitochondria Serving For Cancer: Metabolic Dysregulationmentioning
confidence: 99%